Effect of different Levels of Urea and Carob Cack on Digestion and growth raste in sheep. - Bin eamir, Muhamad Alsanusaa (Al-Mukhtar Journal of Sciences, 1992)
Comparative feeding trial and concurrent digestibility experiment conduct ed to test the effects of different levels of Urea on the Performance of sheep expressed as apparent digestibility of Dry matter, Nitrogen balance, average daily gain and blood measurements, when Urea was used as protein supplement supported with Carob Cack (Caroba - Caroba) as an energy Source. Four different isonitrogenous diets with the same TDN were used each des. ignated to a group of three heads of sheep. Rations A, B, C, and D contained Ziro, 1%, 2%, and 3% Urea respectively. Percent Protein content and TDN were 14.5% and 60% respectively. The periods of Experiments were 63 days for feeding trial and 40 days for digestibility and Nitrogen balance. Results indicated no significant difference in dry matter digestibility (DMD) or Nitrogen balance between ration A (control) and rations B and C, However there was a significant drops in DMD and Nitrogen balance when Urea percent increased up to 3% (Ration D). The Optimum positive response in respect to body gain, DMD and Nitrogen balance was obtained at levels of 10% Carob Cack and 2% Urea as an energy and protein supplements respectively. Blood picture (PH hemoglobin content, RBC and WBC counts) in control and treated animals was significantly affected by different levels of Urea, however differences between different levels of Urea was not significant. Results conclude that Urea can be used in levels of 1% to 2% in Sheep ra. tions and best performance of sheep are obtained when this levels of Urea supplemented with 10% to 15% crushed Ca. rob Fruit.